Morpho-physiological diversity in the collection of sour cherry (Prunus cerasus) cultivars of the Fruit Genebank in Naoussa, Greece using multivariate analysis - Ioannis Ganopoulos (2018)
© 2016 Elsevier B.V. The phenotypic characterization of sour cherry cultivars provides important information on their attributes, which is of paramount importance for their breeding and germplasm management. This study examined the Hellenic Sour Cherry Genebank, which consists of 27 sour cherry cultivars, located in the Institute of Pomology Fruit Genebank, Naoussa, Greece. The data analyzed in this study were obtained after a ten-year consecutive monitoring of 38 morpho-physiological descriptors of phenology, plant morphology, yield and fruit quality. For the statistical analysis were applied hierarchical cluster analysis and principal component analysis (PCA). According to the analysis, the descriptors demonstrated a high degree of variability, especially, yield, ratio of titratable acidity and soluble solids, number of flower buds, and pit weight. Moreover, the variables fruit equatorial diameter, fruit width, fruit weight, fruit size, fruit shape and lamella shape characters exhibited high discriminating power. Significant positive and negative correlations were detected as well among the studied quantitative traits. The highest significant positive correlation was found between the fruit equatorial diameter and the fruit width (0.974). Whereas, the highest significant negative correlation was found between the ratio of pit volume to fruit volume and the fruit weight (-0.737). An unsupervised hierarchical cluster analysis was performed using the Euclidean distance and the Ward's agglomeration method. The sour cherry cultivars were classified into three main clusters, suggesting that the characterized sour cherry collection has a high potential for specific breeding goals. We discuss the usefulness of the identified correlations among the traits, for potential breeding projects regarding fruit size and quality.